Small bowel obstruction caused by a bezoar following an adult simultaneous liver-kidney transplantation: A case report - Pan, Gilbert (World J Clin Cases, 2020)
BACKGROUND: Small bowel obstructions (SBOs) are common following a large intra-abdominal operation; however, SBOs caused by bezoars are unreported in patients following liver-kidney transplantation procedures, particularly in adults. CASE SUMMARY: A 65-year-old Caucasian female presented with nausea and nonbilious emesis during her postoperative course following a simultaneous liver-kidney transplantation. She developed worsening nausea and vomiting with significant abdominal distension and obstipation. Computed tomography imaging showed a marked abnormal dilation of multiple small bowel loops with a distinct transition point that was suggestive of a small bowel obstruction. An exploratory laparotomy revealed a foreign body in the intestinal track approximately 30 cm from the ileocecal valve. The foreign body was extracted and identified as a bezoar with hair follicles and old digestive contents. Following the operation, the patient demonstrated rapid clinical improvement with resolution of nausea, emesis, and progress in bowel motility. CONCLUSION: SBOs caused by bezoars can occur immediately following a liver-kidney transplantation and should not be discounted as a diagnosis.